2009
DOI: 10.1021/jp900136q
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Photocatalytic Activity of Mesporous TiO2 Powders by Hydrothermal Surface Fluorination Treatment

Abstract: Mesporous surface-fluorinated TiO 2 (F-TiO 2 ) powders of anatase phase with high photocatalytic activity are prepared by a one-step hydrothermal strategy in a NH 4 HF 2 -H 2 O-C 2 H 5 OH mixed solution with tetrabutylorthotitanate (Ti(OC 4 H 9 ) 4 , TBOT) as precursor. The prepared samples are characterized by X-ray diffraction, X-ray photoelectron spectroscopy, N 2 adsorption-desorption isotherms, UV-vis absorption spectroscopy, and transmission electron microscopy. The production of hydroxyl radicals ( • OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
377
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 594 publications
(410 citation statements)
references
References 73 publications
13
377
8
Order By: Relevance
“…The as-prepared anatase TiO 2 presented a 140.1 m 2 /g BET surface area, 5.44 nm pore diameter and 0.19 cm 3 /g pore volume. The surface fluorination resulted in a sharp drop in the BET surface area but a sharp increase in the pore size and pore volume of F-TiO 2 due to growth of TiO 2 crystallites [23,39]. In contrast, the defluorination process did not induce much difference in BET surface area, pore diameter and pore volume of samples.…”
Section: Bet Surface Area and Pore Size Distributionmentioning
confidence: 89%
See 1 more Smart Citation
“…The as-prepared anatase TiO 2 presented a 140.1 m 2 /g BET surface area, 5.44 nm pore diameter and 0.19 cm 3 /g pore volume. The surface fluorination resulted in a sharp drop in the BET surface area but a sharp increase in the pore size and pore volume of F-TiO 2 due to growth of TiO 2 crystallites [23,39]. In contrast, the defluorination process did not induce much difference in BET surface area, pore diameter and pore volume of samples.…”
Section: Bet Surface Area and Pore Size Distributionmentioning
confidence: 89%
“…The fluoride peak at binding energy 684.5 eV (F 1s) only appears in the F-TiO 2 sample, indicating the formation of surface fluoride ( Ti-F) by a ligand exchange reaction between F − and the surface hydroxyl group on the TiO 2 surface [40][41][42][43][44]. No peak for F − ions in the lattice at 688.5 eV was observed in the spectra, because the hydrothermal process could prevent the substitution of F − for O 2− in the lattice of TiO 2 [21,39,40,45]. The fluoride peak in the D-TiO 2 almost disappeared after defluorination, indicating that the surface fluorine atoms were removed by NaOH washing for 10 h [46].…”
Section: Xps Analysismentioning
confidence: 99%
“…The enhancement in the H 2 evolution in presence of graphene in TiO 2 could be due to excellent electron accepting and transferring capability, and the capacity to restrain the recombination of the photo-excited electrons and holes effectively. It has been reported that the two-dimensional π-conjugation structure of graphene sheets facilitates the transfer of photo-induced electrons and can act as an excellent electron acceptor [57,58]. A further increase in graphene content leads to a reduction of the photo-catalytic activity.…”
Section: Photo-catalytic Hydrogen Evolution From Plasmonic Active Phomentioning
confidence: 99%
“…Peaks at 3400, 2930, 2850 cm −1 are attributed to the Ti-OH bond [39]. The TiO 2−x N x sample shows additional peaks at 1450, 1160 cm −1 attributed to nitrogen atom in the TiO 2 matrix [40]. The peak at 600 cm −1 can be assigned to the absorption bands of Ti-O and O-Ti-O.…”
Section: Ftir Analysismentioning
confidence: 99%
“…The practical applications of TiO 2 have been suppressed by the low quantum yield that arises from the rapid recombination of photo-induced charge carriers and the other drawback is the poor solar absorption efficiency that is determined by its band gap. It was found that doping with nonmetals (e.g., boron [4], carbon [5], nitrogen [6] and fluorine [7]), especially nitrogen can successfully modify the electronic structure of TiO 2 , extending the photoresponse of TiO 2 to the visible light region. Many studies have been reported that loading of noble metals (e.g., Pt, Au, or Ag) on the surface of TiO 2 can effectively hinder the recombination and promote the transfer of photo-induced electrons to these metal deposits [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%